2020
DOI: 10.1039/c9ra10218c
|View full text |Cite
|
Sign up to set email alerts
|

Non-covalent interactions between sertraline stereoisomers and 2-hydroxypropyl-β-cyclodextrin: a quantum chemistry analysis

Abstract: Inclusion compounds formed between sertraline stereoisomers and β-cyclodextrin, and 2-hydroxypropyl-β-cyclodextrin, were analyzed by using quantum chemistry methods.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(15 citation statements)
references
References 39 publications
0
14
0
Order By: Relevance
“…Later, in 2010, it was compared with Glycam06 FF and defined as far less accurate [44]; the newest computational approaches and the increasing computational power shed new light on this abandoned carbohydrate FF. In 2020, an article applying the MM3 FF for the MD simulation of CD and sertraline was published [45]. According to our best knowledge, it is the only example of MM3 application in the CD MD simulations.…”
Section: Force Fields Dedicated To Cyclodextrinsmentioning
confidence: 99%
See 2 more Smart Citations
“…Later, in 2010, it was compared with Glycam06 FF and defined as far less accurate [44]; the newest computational approaches and the increasing computational power shed new light on this abandoned carbohydrate FF. In 2020, an article applying the MM3 FF for the MD simulation of CD and sertraline was published [45]. According to our best knowledge, it is the only example of MM3 application in the CD MD simulations.…”
Section: Force Fields Dedicated To Cyclodextrinsmentioning
confidence: 99%
“…As a result, the application of such FFs is much more computationally expensive. As stated above, among all gathered from the articles in this literature review, there is only one in which MM3 FF is used [45]. These calculations are run with the Tinker code [47].…”
Section: Force Fields Dedicated To Cyclodextrinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Lately, the interactions between antidepressant drugs and cyclodextrins were examined [22][23][24][25][26], mostly in order to gain the better water solubility of the drug [27][28][29], or to decrease its toxicity [30,31] or even for taste-masking [32]. One of the antidepressants, sertraline hydrochloride, belonging to the class of selective serotonin reuptake inhibitors (SSRIs) [33,34] and also tested as potential anti-Helicobacter pylori compound [35] has already been tested in the presence of β-cyclodextrin and the derivatives [36][37][38][39][40] inter alia in our laboratory [31,41,42].…”
Section: Introductionmentioning
confidence: 99%
“…Quite recently Bautista‐Renedo et al reported a detailed study about the interactions observed between β CD, and 2‐hydroxypropyl‐ β CD (HP‐ β CD), with sertraline (SRT) [23], which is an inhibitor of serotonin to relieve some depressant symptoms [24–27]. In this study, the CMD was coupled with some quantum chemistry methods to reveal the interactions that command on some host‐guest adducts.…”
Section: Introductionmentioning
confidence: 99%